A aurora e o crepúsculo perspectivas para o plano de restauro e centenário do Palácio da Intendência de Cruz Alta/RS, um patrimônio tombado - Hinning, Josiane de Oliveira Pillar (2013)
The cultural value of a good is not reduced to just what can be clearly seen through the architecture or material heritage, but through observation and day-by-day experience. More accurately, it is possible to notice many other special aspects and share and sensitize other actors, which is the greatest challenge. Palácio da Intendência de Cruz Alta (current City Hall building), in Brazil, has the vocation to be an instigating place. The building, since its conception in the first decade of the twentieth century, stands out because of its unique architecture. Many other possibilities surround this piece, often remembered for its eclectic architecture. Designed by German architect Theodor Wiederspahn, it is a fascinating example of positivist architecture, with harmonic lines, richly ornamented and permeated by symbologies. After nearly a century of its inauguration, the place suggests and challenges the research, the heritage education and it seeks for valorization initiatives. The building, heritage of Cruz Alta, is a property listed by Patrimônio Histórico e Artístico do Estado IPHAE (department of historical and artistic heritage of the State). It is a rich, dynamic and unique object of studies that requires a more dedicated eye with proposals of actions to highlight such values. This patrimony shows a number of features that will be discussed in this study, elucidating both aspects of the listed good s architecture, highlighting the decorative ornaments and their signs, and the approach of the current condition and the noted potential to be explored and highlighted. The intention is to bring up the discussion about the collective construction of a knowledge on patrimony. Seeking to understand the existent situation, widening the debate to construct guidelines for Plano de Restauro (Restoration Plan), the building is a symbol of power and houses the City Hall of Cruz Alta/RS, in Brazil, today. Through the awakening to a critical consciousness it is possible to amplify actions on behalf of heritage in several areas, due to the perspective that involves the appreciation of the memory and identity, the aurora toasting a new daylight.